2017
DOI: 10.4236/ojog.2017.75059
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body Mass Index on Assisted Reproductive Treatments

Abstract: Multiparity amongst women with a body mass index (BMI) ≥ 30 Kg/m 2 is a common occurrence despite there being a known clear association with a decline in fecundity in women who are overweight or obese. These women, also pose further concerns, as they are at increased risk of antenatal complications such as preeclampsia and gestational diabetes. Over the years, a number of different modalities of fertility treatments have been tried and tested in this cohort of women to find the optimal treatment to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(25 reference statements)
2
0
0
Order By: Relevance
“…However, the difference recorded among patients with a BMI of at least 30 was statistically significant ( P =0.024). The results of the study are consistent with previous studies …”
Section: Pregnancy Ratessupporting
confidence: 93%
See 1 more Smart Citation
“…However, the difference recorded among patients with a BMI of at least 30 was statistically significant ( P =0.024). The results of the study are consistent with previous studies …”
Section: Pregnancy Ratessupporting
confidence: 93%
“…The results of the study are consistent with previous studies. [2][3][4] The present study demonstrated an inverse relationship between increasing BMI and pregnancy rate in patients with infertility. With increasing obesity prevalence worldwide, and especially in the gulf region, pre-conception counseling and weight loss are highly recommended before using assisted conception methods to optimize outcomes.…”
supporting
confidence: 59%